2020
DOI: 10.3390/foods9091202
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Strategies to Reduce Acrylamide Formation in Californian-Style Green Ripe Olives

Abstract: Acrylamide, a compound identified as a probable carcinogen, is generated during the sterilization phase employed during the processing of Californian-style green ripe olives. It is possible to reduce the content of this toxic compound by applying different strategies during the processing of green ripe olives. The influence of different processing conditions on acrylamide content was studied in three olives varieties (“Manzanilla de Sevilla”, “Hojiblanca”, and “Manzanilla Cacereña”). Olives harvested during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
(54 reference statements)
6
20
1
Order By: Relevance
“…This elaboration process involves oxidation with air, treatment with sodium hydroxide, washing phases, the addition of ferrous gluconate, and thermal sterilization (121 °C during 20–30 min). In this sense, different strategies have been proposed to mitigate the presence of this toxic substance during its industrial processing [ 13 , 14 ]. These strategies are based on the reduction of the precursor of this pollutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This elaboration process involves oxidation with air, treatment with sodium hydroxide, washing phases, the addition of ferrous gluconate, and thermal sterilization (121 °C during 20–30 min). In this sense, different strategies have been proposed to mitigate the presence of this toxic substance during its industrial processing [ 13 , 14 ]. These strategies are based on the reduction of the precursor of this pollutant.…”
Section: Discussionmentioning
confidence: 99%
“…A European recommendation [ 11 ] indicates that authorities must control the acrylamide level in olives stored in brine solutions on an industrial scale. In this sense, several results in the literature apply different mitigation strategies to reduce acrylamide levels during the industrial elaboration process of Californian-style black [ 4 , 5 , 12 , 13 ] and green olives [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the health risks associated with acrylamide ingestion, reducing acrylamide content in foods has become one of the most important issues in food safety. A number of strategies have been proposed to control acrylamide levels in processed foods, including replacing food materials with those has low acrylamide precursor content, such as selecting potato cultivars with low concentrations of reducing sugars or changing harvest time and storage conditions ( 9 , 10 ); reducing the amount of acrylamide precursor, such as application of L- asparaginase in foods ( 11 ); pretreatment of food materials, such as washing olives with water at 25°C before lye and thermal treatment, or immersing potato slices in different solutions before frying ( 12 , 13 ); regulation of food processing conditions, such as lower temperature and shorter processing time ( 14 ); and applying functional food ingredients to prevent acrylamide formation, such as amino acids. Kobayashi et al ( 15 ) found lysine and cysteine mediated acrylamide content reduction in aqueous solution below 120°C.…”
Section: Introductionmentioning
confidence: 99%
“…Acrylamide in foods is mainly produced as a result of the reaction between asparagine amino acid and reducing sugars in the Maillard reaction, although different mechanisms appear to be involved in the formation of acrylamide in table olives (Casado et al, 2013;Charoenprasert and Mitchell, 2014). A wide range of acrylamide concentrations have been described in Californian ripe olives, ranging from 44 to 210 ng g-1 in green ripe olives (Charoenprasert and Mitchell, 2014;Martín-Vertedor et al, 2020) to higher values in black olives or black ripe olives (30 to 1000 ng g-1) (Charoenprasert and Mitchell, 2014;Martín-Vertedor et al, 2020;Pérez-Nevado et al, 2018). Until now, the aforementioned European regulation does not include benchmark levels for acrylamide in table olives (EC, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have suggested that traditional table olive processing methods should be modified in order to ensure lower acrylamide levels. In a previous study, Martín-Vertedor et al (2020) evaluated the effect of the ripeness stage, washing prior to lye treatment, presentation format and additives on acrylamide content in Californian-style green ripe olives. However, to our knowledge, such information does not exist for Californian-style black ripe olives.…”
Section: Introductionmentioning
confidence: 99%